Perencanaan Saluran Drainase Jalan Meranti Darat dan Laut Kota Dumai - Santoso, Aji; Putra, Sony Adiya; Halimatusadiyah; Desriyati, Welly (SLUMP TeS : Jurnal Teknik Sipil, 2024)
Floods caused by natural factors such as sea tides, rainfall, the influence of land characteristics, erosion, sedimentation, decreased river capacity, and insufficient drainage capacity. The aim of this research is to understand the factors that cause flooding and inundation on the Meranti land and sea roads. This drainage planning uses the Gumbel Method. The cause of flooding on the Meranti Land and Sea roads is due to the drainage being unable to accommodate the inundation that occurs, The flood plan discharge obtained exceeds the existing channel cross-sectional discharge, namely Qt (5,012 m3/second) > Qs (4,947 m3/second). The planned cross-sectional capacity of the channel is square, for the channel has b = 3.5 m, h = 1.5 m, w = 0.866 m, From the calculation results, the channel discharge can accommodate the planned flood discharge that occurs, namely Qt (5,012 m3/second) > Qs (6,078 m3/second). For further research at the land Meranti and sea Meranti locations, researchers are expected to calculate the delivered water or tidal water from the sea, whether the channel is able to accommodate water sent from the sea or not.